2008
DOI: 10.1590/s1516-35982008000900004
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de cama sobreposta de suínos e sobressemeadura de leguminosas para aumento da produção e qualidade de pastagem natural

Abstract: RESUMO -Este trabalho foi conduzido com o objetivo de verificar o efeito da fertilização com dois tipos de camas sobrepostas de suínos (CSS), à base de casca de arroz (CA) e maravalha (MA), sobre a produção de uma pastagem natural, com predomínio de Axonopus sp. e Paspalum sp., sobressemeada com leguminosas (cornichão e trevo-branco). As camas sobrepostas foram aplicadas em quantidades equivalentes a 180, 360, 540 e 720 kg/ha de P 2 O 5 , constituindo quatro níveis de cama de casca de arroz (30, 60, 90 ou 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
1
1
Order By: Relevance
“…The −Legume pastures exhibited significantly increased microbial PLFA abundance, SOC, TN, and SOM in response to +Compost treatments, but no significant differences between +Compost and −Compost treatments were observed in +Legume pastures (Table 2, Figures 1b,3b,and 4b). Although some studies have shown impacts of compost on legume production (Hentz, Scheffer-Basso, Escosteguy, & Fontaneli, 2008), we observed no consistent effects of compost addition on forage biomass collected during each summer sampling event (data not shown) that would explain our results. We were able to estimate plant biomass and composition in 1-m −2 subplots at each summer soil sampling date during early season plant growth, but not in the fall because of hay cutting immediately preceding each fall sampling date.…”
Section: Response To Compost Modified By Pasture Managementcontrasting
confidence: 82%
“…The −Legume pastures exhibited significantly increased microbial PLFA abundance, SOC, TN, and SOM in response to +Compost treatments, but no significant differences between +Compost and −Compost treatments were observed in +Legume pastures (Table 2, Figures 1b,3b,and 4b). Although some studies have shown impacts of compost on legume production (Hentz, Scheffer-Basso, Escosteguy, & Fontaneli, 2008), we observed no consistent effects of compost addition on forage biomass collected during each summer sampling event (data not shown) that would explain our results. We were able to estimate plant biomass and composition in 1-m −2 subplots at each summer soil sampling date during early season plant growth, but not in the fall because of hay cutting immediately preceding each fall sampling date.…”
Section: Response To Compost Modified By Pasture Managementcontrasting
confidence: 82%
“…Organic fertilizers contain highly variable concentrations and rates of nutrient release in the soil, and for pig deep-litter (PDL) there are still no indices of availability (IA) of the main nutrients, such as nitrogen, phosphorus and potassium (Hentz et al, 2008). As the PDL system is recent, little is known about the quantities to be used in crops, exclusively or associated with NPK fertilization.…”
Section: Introductionmentioning
confidence: 99%